A comparison of prescribing and non‐prescribing nurses in the management of people with diabetes. (21st September 2015) - Courtenay, Molly; Carey, Nicola; Gage, Heather; Stenner, Karen; Williams, Peter
Abstract: Aim: The aim of this study were to compare nurse prescribers and non‐prescribers managing people with diabetes in general practice regarding: (a) patient characteristics; (b) activities and processes of care; (c) patient outcomes (self‐management, clinical indicators, satisfaction) and (d) resource implications and costs. Background: Over 28, 000 nurses in the UK can prescribe the same medicines as doctors provided that it is in their level of experience and competence. Over 30%, mostly in general practice, prescribe medicines for patients with diabetes. Design: A comparative case study. Method: Nurses managing care of people with Type 2 diabetes were recruited in twelve general practices in England; six could prescribe, six could not. Patients, recruited by nurses, were followed up for 6 months (2011–2012). Results: The patient sample comprised 131 in prescriber sites, 83 in non‐prescriber sites. Patients of prescribers had been diagnosed and cared for by the nurse longer than those of non‐prescribers. There were no differences in reported self‐care activities or HbA1c test results between the patients of prescribers and non‐prescribers. Mean HbA1c decreased significantly in both groups over 6 months. Patients of prescribers were more satisfied. Consultation duration was longer for prescribers (by average of 7·7 minutes). Non‐prescribing nurses sought support from other healthcare professionals more frequently. Most prescribing nurses were on a higher salary band than non‐prescribers. Conclusion: Clinical outcomes of patients managed by prescribing and non‐prescribing diabetes nurses are similar. Prescribing nurses had longer relationships with their patients and longer consultations, possibly contributing to higher satisfaction with care. Employment costs of prescribing nurses are potentially higher.